Desarrollo urbano y desigualdad en el área periurbana de Carabayllo - Ramirez Bautista, Bernardino (2007)
The research shows the process of urbanization of the periurbana area of Carabayllo, district located in Metropolitan Lima. One studies the earth market, the urban occupation of agricultural lands and opens of terrain, the problem of the house, the social and economic situation of the families, the state of the health and the education, the availability of the basic services and the configuration of the social inequality.